Big data : information in the digital world with science activities for kids - Mooney, Carla, 1970- ("Build it yourself" series., 2018)
Offers readers and students ages ten to fifteen lessons and resources to explore big data and information in the digital world, discussing how digital data is essential to everyday life in the modern world. Throughout there are STEM experiments readers can do that offer hands-on problem-solving opportunities that illustrate how understanding digital data can help them be better digital citizens.